(untitled) (Medico Legal Update, 2021)
In the general population Thyroid dysfunctions are common after DM as the most well-known situation to influence the endocrine system. Diabetic patients are at increased danger of thyroid sickness, particularly persons with poor glycaemic control. Ischemia Modified Albumin IMAis novel marker of oxidative stress and tissue ischemia . The pathophysiological occasions of ischemia, including free oxygen radicals and hypoxia, bring about a conformational change of albumin in the N-terminus. The study included 120 subjects, divided into four groups; the first group included 30 patients type2 diabetes mellitus T2DM with newly diagnosed hyperthyroidism HprT, the second group includes 30 patients T2DMwith newly diagnosed hypothyroidism HpoT, the third group included 30 patients diagnosed with T2DM, and the fourth group included 30 healthy control subjects. The concentration of (fasting blood glucose FBG, Glycated hemoglobin HbA1c,Total cholesterol TC, Triglyceride TG,high density lipoprotein HDL, Free Triiodothyronin FT3,Free Thyroxin FT4 and thyroid-stimulating hormone TSH). The results show high significant differences in level of IMA between all studied groups that including diabetic patient with newlydiagnosed hyperthyroidism, diabetic patient with newlydiagnosed hypothyroidism, DM only, and control group [(2.60±1.11), (2.41±1.23), (2.57±5.50), (2.10±0.61)] respectively. Conclusion: Biomarkers IMA could be helpful early diagnosis in monitoring T2DM with newlydiagnosed thyroiddisorders.